PENGARUH DISIPLIN KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI DINAS PERTANIAN PETERNAKAN PERIKANAN DAN KEHUTANAN KOTA JAMBI - Rinoldy, Z (Jurnal Dinamika Manajemen, 2013)
The purpose of of this research is to examine the influence of work descipline and Work Competencies on Employee Performance Agriculturalâ€™s Fishery and Forest Office in City of Jamb. Research type that counducted is survey where officeâ€™s employee chousen to be sample. Results shows that work desipline and work work competencies effect employee performance significantly. Hence, it is recommended the management to improve the competencies and descipline to improve the performance. Key Words. SKPD, work competencies, work descipline and and organization Â